Sovereignty Re-Examined: The Courts, Parliament, and Statutes - Barber, N (Oxford University Press, 2000)
In this article the relationship between Parliament and courts is examined. The views of writers on sovereignty are considered and criticized. Two criticisms of the sovereignty theorists are made: first, that they wrongly assume that a legal system must attribute supreme legal power to a single source and, second, that they wrongly assume that statutes in the English system constitute absolute exclusionary reasons for decision. It is contended that legal systems, can, and the English Constitution does, contain multiple unranked sources of law. Hart's rule of recognition and Kelsen's Grundnorm are considered and compared, and found to be insufficiently flexible to meet the realities of the English Constitution. A more complicated model of judicial reactions to statutes is proposed, and decisions of the judges that run contrary to the law as set down in the statute are considered. It is contended that the relationship of the courts to Parliament ought not to be considered a purely legal issue; it also has a political dimension. The paper should now be read alongside Barber, 'The Afterlife of Parliamentary Sovereignty' (2011) 9 International Journal of Constitutional Law 144-154, and Barber, The Constitutional State (Oxford: Oxford University Press, 2010), chapters 5, 6, and 9.